Measuring outcomes of rehabilitation among the elderly—a feasibility study - Pitkänen, Laura J.; Niskanen, Jyri; Malmivaara, Antti; Torkki, Paulus (Frontiers in Health Services, 2023)
A feasible system for measuring patient outcomes of rehabilitation is required for assessing the real-world cost-effectiveness of rehabilitation. This study aims to assess the feasibility of measuring outcomes of rehabilitation among elderly individuals with early-stage Alzheimer’s. We used the principles of Design Science to construct a set of metrics consisting of standardized PROM (Patient-Reported Outcome Measure) questionnaires, clinician-reported measures, and observational measures of functioning. We used standardized questionnaires whenever possible to ensure the validity and reliability of the questionnaires. The set of metrics was piloted on 16 individuals living at home with regular home care services. After the pilot, we further refined the set of metrics based on relevance, sensitivity to change, and applicability. We found that measurement was feasible and we propose the final set of metrics as a minimum set, which could be further improved upon by addition of metrics relevant to each subgroup of elderly individuals. We also found that using self-reported questionnaires in this population is not without difficulties. We therefore suggest that the role of informal caregivers be considered, and that accessibility of outcome questionnaires be improved.